Study of Delay Analysis in Residential Building Project Fuzzy Approach: Examining factors influencing construction delays using a fuzzy approach (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Due to the inherent risks and increasing complexity of modern construction projects, industry delays and cost overruns have become commonplace. Researchers and practitioners used a number of methods to assess the liability of project delays and fear delays among the participating parties. Survey base delay analysis is considered to be one of the most reliable methods to analyze construction delay. Despite its advantages, survey analysis can give different results depending on the amount of data collected, which can be considered as acceleration by the employer and the contractor, as well as the impact of many infrastructure upgrades made due to changes in the logical relationships of duration and operations in a systematic way. , And the impact of progress events on the over-allocation of resources can be considered and consequently delayed. This study proposes a survey basis on analytical models that can consider several factors influencing construction delay. In this work we have proposed a blurred base waiting and recommendation approach, which can take into account many of the factors included in the survey. Finally the system recommends various ranking factors that cause delays along the graph. Mixed research applies to any type of construction project.